Study of appropriate timing and short term effectiveness of measles vaccination - Dr Vani HN; Dr Guruprasad G; Dr Abdul Manaf K.M (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Measles remains the leading cause of vaccine preventable childhood mortality and morbidity in developing countries. Measles vaccine contributes to the reduction of childhood mortality. The optimal age of vaccination has to be individualised for each country.Materials and Methods: The study was done for a period of two months in a government hospital Davangere. A total of 84 children were studied in three groups. Group 1 comprised of 29 children, of 9 months (± 10 days) of age, not vaccinated against measles. Group 2 of 28 children of 18 months (± 15 days) of age, vaccinated against measles at 9 months of age. Group 3 of 27 children of 36 months (± 15 days) of age, vaccinated against measles (EZ strain) at nine months of age. Antibody titres more than 200mIU/ml, was considered seropositive and statistical analysis was done by ANOVA and Mann Whitney test, chi square test.Results: In group 1, 13 (45%) of 29 children were seropositive, 55% were seronegative, and 8 (28%) had antibody level above 1000 m IU/ml. In group 2, 7(26%) were seronegative. In group 3, 5(18%) were seronegative. Antibody titres had significant statistical variation between groups 1 and 2, and groups 1 and 3. Sex, nutrition status and duration of exclusive breast feeding did not have any influence in the seropositivity in all the three age groups.Conclusion: Measles vaccine should be administered before 9 months, as early as 6 months and second dose at 12-15 months of age.